A rare anatomical variation of the bile ducts: Cystic duct draining to the right hepatic duct - Feyyaz Güngör,; Yunus Sür,; Emine Özlem Gür,; Osman Nuri Dilek, (Turkish Journal of Gastroenterology, 2019)
Cite this article as: Güngör F, Sür Y, Gür EÖ, Dilek ON. A rare anatomical variation of the bile ducts: Cystic duct draining to the right hepatic duct. Turk J Gastroenterol 2019; 30(4): 375-6.